Back to the Past: Social Community Interaction Pattern in Braga Creative Tourism Urban Village - Andika, Vania Claresta; Hermawan, Daniel (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This research aims to be able to analyze the interaction patterns that occur in Braga Creative Tourism Urban Village. Social interaction, community, stakeholders, and community empowerment are the theoretical basis for this research. Research methods: The research method used is descriptive qualitative research with data collection techniques, namely interviews, observation, and documentation. Data credibility uses triangulation (sources and methods) and documentation studies. Data collection was carried out until it reached the data saturation point. Results and discussion: The results of the analysis in this study show that the interaction patterns that occur in Braga Creative Tourism Urban Village are familiar in nature. In conclusion, the Braga Creative Tourism Urban Village program has a very good goal to be implemented in the Braga location which has great potential or opportunity to empower the community to become a self-sufficient society. However, running the Braga Creative Tourism Urban Village program requires clear direction and execution and has standards, so that the progress of the program can run optimally. Implication: The implication for growth and development in Braga Creative Tourism Urban Village for Pokdarwis is by conducting professional training, consistent content schedules, advertising on social media, and creating tour packages that have a clear price structure. Other implications for the government to develop Braga Creative Tourism Urban Village by collaborating with the education sector, holding sharing forums, and providing awards for Pokdarwis members.